الدعم التنظيمي المدرك ودوره في تعزيز التماثل التنظيمي لدى الأستاذ الجامعي - دراسة حالة كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير جامعة ورقلة- - تيشات, سلوى; مزهودة, نور الدين (جامعة الوادي - University of Eloued, 2021)
This study aims to identify the role of perceived organizational support in enhancing organizational identification among the professors of the Faculty of Economics Sciences, and Commercial Sciences and Management Sciences at the University of Ouargla. So as to achieve study objectives the researchersused the questionnaire as a main tool to collect datawere analyzed by using the Statistical Package for Social Sciences (SPSS). The study has reachedseveral conclusions, the most important of which are: Thereis a positive relationshipbetweenperceived organizational support and organizational identificationamong the professors of the Faculty ofEconomics Sciences, and Commercial Sciences and Management Sciences at the University of Ouargla
Perceived organizational support and its role in enhancing the organizational identification of the university professor -Case study Faculty of Economic Sciences and Commercial Sciences, and Management Sciences - University of Ouargla-
مقال
Keywords: دعم تنظيمي مدرك ; تماثل تنظيمي ; أستاذ جامعي